Economics, Academics and Entrepreneurial Inadequacy in Kenya - Iraki, X. N. (Archives of Business Research, 2018)
There is belief that Kenyans who pursue higher degrees, specifically PhD are not entrepreneurial and use qualifications to mask their “entrepreneurial inadequacies”. This paper investigates this belief by using empirical data collected from a sample of PhD students in one Kenyan university. The study analyzes the entrepreneurial activities of the sample based on gender, age, undergraduate specialization, exposure (proxied by travelling abroad), professional orientation and social mobility (proxied by their current position in the organizations they work). The study is cross-sectional, and finds that most students are pursuing a PhD not because of “entrepreneurial inadequacy” but have capacity in terms of time, energy and some money. Self actualization and creating a “hedge” against unemployment and retirement are other reasons driving Kenyans, whose average age is about 40 years into classroom. The amount of money they make from “side hustles” leaves no doubt that they did not get into entrepreneurship by chance or desperation. The study further debunks the myth that entrepreneurship is for “failures.”